Das Representações Numéricas Inatas à Matemática Culturalmente Construída - Andrade, Paulo Estêvão; Do Prado, Paulo Sérgio Teixeira [UNESP]; Dos Santos Carmo, João (Associacao Brasileira de Psicologia, 2015)
Data from recent research in cognitive psychology, neuropsychology and cognitive neuroscience has allowed a growing consensus that the numerical representations in adults and the culturally constructed mathematical thinking depend on the interaction between the so-called number sense, observed in human babies and in other animal species, and the language. In research with babies, the technique of preferential looking has allowed the discovery of sophisticated skills in early ages, among them those of addiction and subtraction. The neuropsychology presents cases of lesions in areas of the brain that cause damage to specific skills, with preservation of others. And cognitive neuroscience, by means of neuroimaging features modern, has allowed the precise location of brain areas responsible for numeric processing. All these contributions shed light on the nature of numerical cognition underlying mathematics. Data produced by those areas are presented and discussed research, as well as its implications for the classical theory of cognitive development and the concept of number in particular. It discusses also the vision arising on the relationship between biology and culture, which will be seen no more as dichotomous way but as a continuation of each other, as well as pedagogical implications and on the training of educators.
From innate numerical representations to culturally constructed mathematics
Keywords: Mathematical thought; Number sense; Numeric representation; Numerical cognition models